IMPROVING TUTORS’ PEDAGOGICAL COMPETENCE THROUGH ONLINE INTERACTIVE LEARNING (SETARA DARING) PLATFORM OPTIMIZATION TRAINING - Sadi Susanto; Ansori Ansori; Sri Nurhayati (Jurnal Visi Ilmu Pendidikan)
This study aimed to investigate the implementation and impact of an online interactive learning platform optimization training program on the pedagogical competence of Package C tutors at PKBM Gagak Mas. Using a case study methodology, data were collected through interviews, observations, and document analysis involving the program manager, three training instructors, and six tutors. The findings revealed significant improvements in tutors' pedagogical competence, including enhanced interactive lesson design, facilitation of online discussions, advanced assessment strategies, differentiated instruction, and effective use of data analytics. Tutors also reported increased confidence in their teaching abilities and received positive feedback from students about the improvements in their teaching methods. This study contributes to the literature on professional development in non-formal education settings by demonstrating the effectiveness of structured, interactive, and supportive training approaches. The findings underscore the importance of tailored training programs that address specific needs and challenges faced by educators. The study's implications suggest that ongoing professional development and support are crucial in equipping tutors with the necessary skills to deliver high-quality online education. Future research should explore the long-term impact and scalability of such training programs to other educational contexts, providing further insights into effective professional development strategies.